2015
DOI: 10.1016/j.eurpsy.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Reported and Intended Behaviour Towards Those With Mental Health Problems in the Czech Republic and England

Abstract: This is one of the first studies, which compares the level of stigmatizing behaviour in countries that used to be on the opposite sides of the Iron Curtain. The aim was to identify the prevalence of reported and intended stigmatizing behaviour towards those with mental health problems in the Czech Republic and to compare these findings with the findings from England. The 8-item Reported and Intended Behaviour Scale (RIBS) was used to assess stigmatising behaviour among a representative sample of the Czech popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 46 publications
2
28
1
1
Order By: Relevance
“…Similar results were found by Högberg et al [39], who found people between 31 and 50 years to be less stigmatizing. In other studies, however, stigmatizing attitudes were found to be increasing with age [41,43] or having no significant influence [8,38,40]. Although in the present study female gender and the age category 35-54 were both found to be significantly associated with less stigmatizing attitudes, the practical meaning of this association is questionable as the total effect size in this regard was rather small.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Similar results were found by Högberg et al [39], who found people between 31 and 50 years to be less stigmatizing. In other studies, however, stigmatizing attitudes were found to be increasing with age [41,43] or having no significant influence [8,38,40]. Although in the present study female gender and the age category 35-54 were both found to be significantly associated with less stigmatizing attitudes, the practical meaning of this association is questionable as the total effect size in this regard was rather small.…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, the ongoing Czech mental health care reform placed stigma high on its agenda [5]. However, stigmatizing attitudes continue to be prevalent world-wide [6,7], despite substantial differences in the level of stigma between individual countries [8].…”
Section: Introductionmentioning
confidence: 99%
“…At the local community level, respondents mentioned lack of understanding and fear of PLs and resulting condemnation and aggressive behavior, which lead to FMs avoiding disclosure of diagnosis. As another recent study documented, 30.8% of the Czech general population are unwilling to have a person with mental illness as a neighbor and 26.4% are unwilling to have one as a friend (Winkler et al, 2015). Evidence of ignorance, misconceptions and endorsement of prejudices was also apparent at the family level, such as beliefs about "infectiousness" of schizophrenia, which reflects a particular example of family beliefs about contagiousness of mental illness (Larson & Corrigan, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, most of this literature on anti-stigma campaigns is coming from Anglo-Saxon countries [16]; and little is known about the effectiveness of these strategies in other countries, which have different cultural values and prevalence of mental disorders [17][18][19].…”
Section: Introductionmentioning
confidence: 99%